2017
DOI: 10.1155/2017/1762047
|View full text |Cite
|
Sign up to set email alerts
|

Anterior-to-Posterior Migration of a Lumbar Disc Sequestration: Surgical Remarks and Technical Notes about a Tailored Microsurgical Discectomy

Abstract: Extrusion of disc material within the spinal canal complicates up to 28.6% of lumbar disc herniations. Due to the anatomical “corridors” created by the anterior midline septum and lateral membranes, relocation occurs with an anterior and anterolateral axial topography. Posterior migration is an extremely rare condition and anterior-to-posterior circumferential migration is an even rarer condition. Its radiological feature can be enigmatic and since, in more than 50% of cases, clinical onset is a hyperacute cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…PEMLDF occurs infrequently because it requires passing through anatomical barriers such as the posterior longitudinal ligament, the peridural and lateral membrane, the epidural venous plexus, epidural fat, the nerve root, and the dura. [ 7 , 8 ] PEMLDF occurs mostly in middle-aged persons (mean age 53.11 years), possibly owing to the dynamics of spinal degeneration associated with aging. [ 5 , 9 ] Most commonly (40% of reported cases), posterior migration occurs at L3-L4, possibly due to the anatomical relationship between the nerve root and disc space in the horizontal plane, which appears to compromise the barrier role of the nerve root at this level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PEMLDF occurs infrequently because it requires passing through anatomical barriers such as the posterior longitudinal ligament, the peridural and lateral membrane, the epidural venous plexus, epidural fat, the nerve root, and the dura. [ 7 , 8 ] PEMLDF occurs mostly in middle-aged persons (mean age 53.11 years), possibly owing to the dynamics of spinal degeneration associated with aging. [ 5 , 9 ] Most commonly (40% of reported cases), posterior migration occurs at L3-L4, possibly due to the anatomical relationship between the nerve root and disc space in the horizontal plane, which appears to compromise the barrier role of the nerve root at this level.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Inflammatory changes in the local environment cause an increase in fluid content in the extruded material, which is responsible for T2 hyperintensity. [ 8 ] Chen et al suggested that high signal intensity on T2-weighted images could be explained as the result of herniated material possessing a higher water content than an intact disc. [ 13 ] Contrast agent must be always used in order to rule out the most common topographical differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…respect to the posterior longitudinal ligament (PLL) is further defined as subligamentous or extraligamentous. A disc extrusion complicates up to 28% of cases of LDH 1 and it usually migrates upward, downward or in the foramina involving the anterior aspect of the spinal canal. [1][2][3][4][5][6] For the management of the cranially migrated sequesters (Fig.…”
mentioning
confidence: 99%
“…A disc extrusion complicates up to 28% of cases of LDH 1 and it usually migrates upward, downward or in the foramina involving the anterior aspect of the spinal canal. [1][2][3][4][5][6] For the management of the cranially migrated sequesters (Fig. 1), the role of the "Translaminar" (or "Transpars") approach is well recognized and defined.…”
mentioning
confidence: 99%